O depósito legal estadual e o registro de direito autoral como mecanismos de proteção da propriedade intelectual de obras bibliográficas do Tocantins - Diniz, Marcelo Neves (Universidade Federal do Tocantins, 2023)
It discusses the protection of intellectual property through a proposed law mechanism for a state legal deposit system containing the copyright registration for the State of Tocantins, where it is also an important instrument for the formation of a heritage collection. The loyal deposit is the sending of copies of any publication produced in a country. In Brazil, the mechanism has been in operation since the imperial period and is currently in force under Law No. National. In addition to the national law, twelve Brazilian states have State Legal Deposit mechanisms, the oldest being the decree of the state of Paraná in 1964 and the most current of the state of Rio Grande do Norte in 2017. In addition to the deposit that helps to form library collections, also helps to preserve memory, thus enabling the control, elaboration and dissemination of current national bibliography, as well as the defense and preservation of the language, safeguarding the memory for the next generations, it also allows the protection intellectual property as a prior registration for copyright, even though its registration with copyright offices is not mandatory. Methodologically, the research is characterized by being of a bibliographic and documentary nature, of an applied nature, with a qualitative approach. It brings a historical approach to the legal deposit and copyright in various biases such as the "Library of Alexandria" as the first depositary unit. It presents the scenario of Legal Deposit mechanisms in Brazilian states. Electronic legal deposit takes place as a factor of technological innovation for access to information and objects of physical and electronic legal deposit. It makes an approach to copyright considering factors on the issue of copyright in the Berne Convention of 1908 and on rights in works produced by machines. It also deals with UNESCO's guidelines for legal deposit and identifies the role of bibliographic control in the preservation of intellectual production heritage. Finally, it brings: a proposal for a decree-law for legal deposit for the State of Tocantins that also addresses copyright protection; strategic tools such as the CANVAS business model and the SWOT matrix and a textbook-format textbook entitled “A guide to copyright registration, legal filing and ISBN application for independent writers: contributions to the protection of Intellectual Property”.